Analisis Pengaruh Perencanaan Strategis SI/TI Dalam Meningkatkan Upaya Keunggulan Bersaing - Cindyasri Pratidina Setyanti; Agustinus Fritz Wijaya (APTIKOM SUMSEL, 2020)
SMKN 2 Salatiga really understands that the role of technology is very important, especially in terms of competition between SMA / SMK equivalents in the Central Java region. This study aims to develop IS / IT strategic planning in competing to increase school excellence, so that data collection is done through interviews, observation, and document study. The data will be taken regarding what factors can be strengths, weaknesses, opportunities, threats, and internal and external environmental analysis at SMKN 2 SALATIGA so that it can identify computer-based application designs that will support the progress of schools in Indonesia. implement a plan of excellence in competition between SMA / SMK and equivalent in Central Java